From productivism to multi-functionality in the Gascoyne-Murchison Rangelands of Western Australia - Hughes, Michael; Jones, Roy (CSIRO Publishing, 2010)
A sustainability assessment of the Western Australian (WA) rangelands identified a range of issues associated with regional economic decline typical of many marginal rangeland regions in Australia. As part of a regional rejuvenation strategy, the WA state government purchased selected pastoral lease properties for incorporation into the conservation estate. It was intended as a means of land-use transition from mono-functional productivism to multi-functionality incorporating protection of significant rangeland bioregions and development of tourism. A 1-year project was conducted to assess the issues relating to this transition. Archived information was obtained from government relating to the characteristics of the lease properties at the time they were purchased. Site visits were undertaken to purchased leases acquired by the government as well as neighbouring leases. During site visits, interviews with pastoralists and purchased lease managers were conducted. A series of facilitated community discussion groups in the region was held to ascertain the views of landholders and managers, government representatives, indigenous interests and commercial operators in the region.This paper describes how the transition to a combination of protection and consumption exchanged one set of problems for another. This was due partly to the intrinsic character of the land, in terms of previous overgrazing, isolation, large distances, and limited infrastructure and services. More importantly, the top-down approach to land transition failed to allocate adequate management resources to replace those lost when the former pastoral leaseholders left. The consequences of inadequate management included theft and rapid degradation of assets, inadequate control of pests and weeds; inadequate fire prevention management and poor communication between the government and other stakeholders over management decisions. This paper discusses the dynamics of this WA rangeland transition with reference to the multi-functional rural transition concept.